Settlement of Sharia Economic Disputes at the Purbalingga Religious Court: Penyelesaian Sengketa Ekonomi Syariah di Pengadilan Agama Purbalingga - Ikhsan Al Hakim (Universitas Negeri Semarang, 2012)
Economic disputes Completion Shariah authority Absolute Being Religious Court. Based on the decision of the Religious Purbalingga archives have completed Shariah economic disputes, than religious courts Ex, residency of Banyumas has never settle economic disputes sharia. The purpose of research is to find out how the existence of religious courts in applying Purbalingga Act No. 3 of 2006 on Religious Courts; factors that affect the high implementation of Sharia Economic Disputes in the Religious Purbalingga compared with the Religious Ex-residency of Banyumas. Research using qualitative methods with socio-juridical approach. Using triangulation techniques. Religious courts Purbalingga has completed 9 (Nine) Islamic economic disputes, 4 finish in peace, and 5 cases granted. compared to the Religious Se-Eks.Karesidenan Banyumas has never settle economic disputes sharia. Purbalingga very existence of religious courts consistently resolve disputes Islamic economics. Factors that support the high courts for dispute Purbalingga are internal and external factors. Internal factors of Human Resources of the Judge, the Registrar, and the Religious Purbalingga bailiff, judge readiness in handling cases of Islamic finance, while the external factors are the subject of one of sharia law of economics that supports the implementation of Shariah Banking Law No. 3 of 2006.